Keeping the Spiritual Home Fires Burning: Religious Belonging in Britain during the First World War. (October 2014) - Field, Clive
Abstract : The religious impact of the First World War on the home front in Britain is assessed in terms of churchgoing and church membership and affiliation. Church attendance rose briefly at the start of the war but fell away thereafter in the Protestant tradition, accelerating a pre-existing trend, which was not reversed after 1918. The disruption caused by the war to the everyday life of organized religion probably accounts for the decrease, rather more than loss of faith. Church membership also declined during the war in the Anglican and mainstream Free Churches, albeit not for other denominations and faiths, but it temporarily revived after the war. This was not the case for non-member adherents and Sunday scholars whose reduction was more continuous.